How common is imaging for low back pain in primary and emergency care? Systematic review and meta-analysis of over 4 million imaging requests across 21 years. Issue 11 (13th February 2019) - Downie, Aron; Hancock, Mark; Jenkins, Hazel; Buchbinder, Rachelle; Harris, Ian; Underwood, Martin; Goergen, Stacy; Maher, Chris G
Abstract : Objectives: To (1) estimate the proportion of patients seeking care for low back pain (LBP) who are imaged and (2) explore trends in the proportion of patients who received diagnostic imaging over time. We also examined the effect of study-level factors on estimates of imaging proportion. Data sources: Electronic searches of MEDLINE, Embase and CINAHL databases from January 1995 to December 2017. Eligibility criteria for selecting studies: Observational designs and controlled trials that reported imaging for patients presenting to primary care or emergency care for LBP. We assessed study quality and calculated pooled proportions by care setting and imaging type, with strength of evidence assessed using the GRADE system. Results: 45 studies were included. They represented 19 451 749 consultations for LBP that had resulted in 4 343 919 imaging requests/events over 21 years. Primary care: moderate quality evidence that simple imaging proportion was 16.3% (95% CI 12.6% to 21.1%) and complex imaging was 9.2% (95% CI 6.2% to 13.5%). For any imaging, the pooled proportion was 24.8% (95% CI 19.3%to 31.1%). Emergency care: moderate quality evidence that simple imaging proportion was 26.1% (95% CI 18.2% to 35.8%) and high-quality evidence that complex imaging proportion was 8.2% (95% CI 4.4% to 15.6%). For any imaging, the pooled proportion was 35.6% (95% CI 29.8% to 41.8%). Complex imaging increased from 7.4% (95% CI 5.7% to 9.6%) for imaging requested in 1995 to 11.4% (95% CI 9.6% to 13.5%) in 2015 (relative increase of 53.5%). Between-study variability in imaging proportions was only partially explained by study-level characteristics; there were insufficient data to comment on some prespecified study-level factors. Summary/conclusion: One in four patients who presented to primary care with LBP received imaging as did one in three who presented to the emergency department. The rate of complex imaging appears to have increased over 21 years despite guideline advice and education campaigns. Trial registration number: CRD42016041987.